Effect of Acetylcholine on Follicle-Associated Peyer’s Patches Epithelium - Alazzamee, Abdulrahman Salim Qatia; Fedorova, Arina Alexandrovna; Markov, Alexander Georgievich (Medical Science Journal for Advance Research, 2025)
The study aims to investigate the regulation of tissue barrier functions by endogenous compounds, particularly acetylcholine, in the intestinal epithelium. The epithelium contains gut-associated lymphoid tissue (GALT), Peyer’s patches (PP), and specialized follicle-associated epithelium (FAE), which play a crucial role in intestinal function and immune responses. The FAE contains microfollicular cells responsible for phagocytosis, transcytosis, and antigen presentation, allowing for controlled uptake of large particles and initiation of an immunological response. The digestive tract is extensively innervated by cholinergic fibers, and acetylcholine (ACh) is a neuroimmunomodulator of the intestinal mucosa. The cholinergic anti-inflammatory pathway is a local anti-inflammatory response in the intestinal mucosa. Peyer’s patches are immune cells that maintain immune tolerance to commensal flora and dietary antigens. The study of barrier functions of the follicle-associated epithelium of Peyer’s patches in the rat small intestine under the action of acetylcholine is currently an understudied problem in gut-associated lymphoid tissue physiology. The aim is to investigate changes in the barrier properties of follicle-associated Peyer’s patches epithelium in the rat small intestine under the action of acetylcholine.